IMPROVING COMMUNITY AWARENESS OF THE MAINSTANDS OF THAHARAH IN WORSHIP - Samsuddin, Samsuddin (Journal of Islam and Science, 2019)
This research discussion about "Increasing Public Awareness of the Priority of Thaharah in Worship in Dua Pitue Sub-District, Sidrap Regency”, as one of the things that has the main position in worship. If someone has understood and implemented thaharah well, worship will be better and vice versa if someone does not understand about thaharah then it could be that his worship is invalid (not accepted) by Allah swt. This study aims to understand (1) How are the virtues of thaharah in worship. The virtue of thaharah in worship is a legal requirement for worship such as one's prayer will not be valid before it is clean from both hadats and impure; (2) What is the level of public awareness of the virtues of thaharah in worship; (3). Factors that influence public awareness of the importance of thaharah in worship and practice thaharah before carrying out worship. Efforts are made to increase public awareness of the importance of thaharah in worship by conducting religious counseling, especially related to the issue of thaharah at least once a month so that community understanding of the virtues of thaharah in worship can be better.